Context dependence of protein misfolding and structural strains in neurodegenerative diseases. Issue 6 (November 2013) - Mehta, Anil K.; Rosen, Rebecca F.; Childers, W. Seth; Gehman, John D.; Walker, Lary C.; Lynn, David G.; Gierasch, Lila; Lynn, David; Schneider, Joel
ABSTRACT Vast arrays of structural forms are accessible to simple amyloid peptides and environmental conditions can direct assembly into single phases. These insights are now being applied to the aggregation of the Aβ peptide of Alzheimer's disease and the identification of causative phases. We extend use of the imaging agent Pittsburgh compound B to discriminate among Aβ phases and begin to define conditions of relevance to the disease state. Also, we specifically highlight the development of methods for defining the structures of these more complex phases. © 2013 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 100: 722–730, 2013.